Splenic lymphoma with villous lymphocytes: clinical presentation, biology and prognostic factors in a series of 100 patients - Xavier Troussard; Françoise Valensi; Éliane Duchayne; Richard Garand; Pascale Felman; M Tulliez; M. Henry‐Amar; PA Bryon; Georges Flandrin (1996)
The diagnosis of splenic lymphoma with villous lymphocytes (SLVL) was assessed by a panel of cytologists in a series of 100 patients. Clinical and biological characteristics were analysed in relation to prognosis. SLVL is a chronic B-cell lymphoproliferative disorder characterized by splenomegaly and the presence, in peripheral blood, of lymphocytes with "villous' projections. The cytological diagnosis can be difficult in patients without an absolute lymphocytosis which was observed in 24% of cases. B-cells expressed CD19+, CD20+, CD22+, CD24+ and DBA44+, whereas the expression of CD5, CD10 and CD25 was usually negative. SLVL is a disease of the elderly with a relatively benign clinical course. In the present series the 5-year overall survival was 78%. Deaths in 15 patients were related to disease progression or treatment (nine cases). Patients with a leucocyte count > 30 x 10(9)/1 or lymphocyte count < 4 x 10(9)/1 or initially treated with chemotherapy had significantly (P < 0.001) lower overall survival than other patients. From these findings, treatment abstention should be considered in patients with favourable prognostic factors; on the other hand, the efficacy of conventional chemotherapy remains to be evaluated in patients with unfavourable prognostic factors.